2020
DOI: 10.1088/1755-1315/461/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on sealing performance of supercritical carbon dioxide compressor dry gas seal

Abstract: Aiming at the serious problem of gap leakage between the stator and rotor of the supercritical carbon dioxide compressor, the dry gas seal scheme for centrifugal compressor of small S-CO2 power system is designed in this paper. The sealing characteristics of the single-stage spiral groove dry gas seal in the S-CO2 operating environment are studied by the large-scale commercial CFD numerical analysis software ANSYS CFX. The leakage characteristics of the S-CO2 dry gas seal at different film thicknesses are obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…At present, a dry gas seal with small leakage is widely used in compressors and turbines as the shaft end seal of equipment. A lot of research work has been done on the structure and performance of dry gas seal. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, a dry gas seal with small leakage is widely used in compressors and turbines as the shaft end seal of equipment. A lot of research work has been done on the structure and performance of dry gas seal. …”
Section: Introductionmentioning
confidence: 99%
“…Muhammad et al 17 proposed a new barrier gas method to reduce the power associated with the leakage supplement system for the sCO 2 turbine and reduced the leakage flow rate from the turbine. Wu et al 18 studied the sealing characteristics of the single-stage spiral groove dry gas seal in the SCO 2 operating environment and found that the dry gas seal leakage flow rate under different film thicknesses is 0.04% to 0.45% of the SCO 2 compressor flow rate. Zakariya and Jahn 19 investigated the supercritical CO 2 dry gas seals operating close to the critical point with an inlet pressure and temperature of 8.5 MPa and 370 K, respectively, and a speed of 30000 rpm and presented the effects of the groove length or dam to groove ratio on the performance of the dry gas seal.…”
Section: Introductionmentioning
confidence: 99%